2002
DOI: 10.1128/aac.46.5.1199-1203.2002
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Group A Streptococcus Strains with Different Mechanisms of Macrolide Resistance

Abstract: The mechanisms of resistance to macrolides in seven group A streptococcal (Streptococcus pyogenes) isolates that were the cause of pharyngitis in children who were unsuccessfully treated with azithromycin (10 mg/kg of body weight/day for 3 days) were evaluated. All posttreatment strains were found to be genetically related to the pretreatment isolates by random amplified polymorphism DNA analysis and pulsed-field gel electrophoresis. Two isolates had acquired either a mef(A) or an erm(B) gene, responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 24 publications
2
48
0
1
Order By: Relevance
“…The numbering of the other lines corresponds to the positions of the nucleotides from the start of the bi-F primer in the sense strand amplicon of the bisulfite reaction ( (39,41,54,55). However, numerous studies have reported that the DNA from some macrolide-resistant isolates is refractory to SmaI digestion (7,22,35,36,44), an observation recently associated with the "M phenotype" of erythromycin resistance, which is imparted by Tn1207.3 or the ⌽10394.4 chimeric element (22,44). The results of our study agree with these reports.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The numbering of the other lines corresponds to the positions of the nucleotides from the start of the bi-F primer in the sense strand amplicon of the bisulfite reaction ( (39,41,54,55). However, numerous studies have reported that the DNA from some macrolide-resistant isolates is refractory to SmaI digestion (7,22,35,36,44), an observation recently associated with the "M phenotype" of erythromycin resistance, which is imparted by Tn1207.3 or the ⌽10394.4 chimeric element (22,44). The results of our study agree with these reports.…”
Section: Discussionsupporting
confidence: 91%
“…One of the most common methods used to examine the clonality of such macrolide-resistant and -sensitive streptococcal isolates involves restriction of genomic DNA with the SmaI endonuclease, followed by pulsed field gel electrophoresis (PFGE) analysis (6,44,55). Recently, however, a number of epidemiological studies have reported that the DNA from a diverse group of erythromycin-resistant streptococci could not be digested with SmaI (7,22,35,36,44). This finding prompted the use of alternative restriction enzymes, such as ApaI, EagI, and SfiI, in the analysis, making it difficult subsequently to directly compare the clonalities of strains that differ in macrolide susceptibility and to relate the results of different epidemiological studies (7,35,36).…”
mentioning
confidence: 99%
“…Our results confirm the importance of using an alternative to bacitracin susceptibility testing. The emergence of strains of S. pyogenes resistant to macrolides has been observed, but they have not been multiresistant to antibiotics (2,9,10,15). In this study, 53 pharyngitis-related and invasive isolates of S. pyogenes resistant to bacitracin were shown to also be resistant to streptomycin, kanamycin, macrolides, lincosamides, and streptogramin B.…”
mentioning
confidence: 64%
“…Mortality due to group A streptococci was 27.3% (6) in adults and 12.1% (4) in children. STSS occurred also more frequently in adults (31.8%) (7) than in children (12.1%) (4).…”
Section: Resultsmentioning
confidence: 97%
“…In gram-positive organisms, erythromycin (ERY) resistance is mediated by either target modification or active efflux (17,29). Target modification may be produced by mutation or by posttranscriptional methylation of adenine molecules in 23S rRNA (4,29). In streptococci, TET resistance is due to active efflux or ribosomal protection (22), while CMP resistance is mediated by target modification, active efflux, or antibiotic inactivation (23).…”
mentioning
confidence: 99%